Ontogeny, evolution and palaeogeographic distribution of the world’s largest ammonite Parapuzosia (P.) seppenradensis (Landois, 1895) - Ifrim, Christina; Stinnesbeck, Wolfgang; González González, Arturo H.; Schorndorf, Nils; Gale, Andrew S. (PLOS ONE, 2021)
The world’s largest ammonite, Parapuzosia (P.) seppenradensis (Landois, 1895), fascinated the world ever since the discovery, in 1895, of a specimen of 1.74 metres (m) diameter near Seppenrade in Westfalia, Germany, but subsequent findings of the taxon are exceedingly rare and its systematic position remains enigmatic. Here we revise the historical specimens and document abundant new material from England and Mexico.
Gesehen am 12.11.2021